Pembelajaran Kitab At-Tadzhib Fi Adillati Al-Ghoyati Wa At-Taqrib Dalam Mengakomodasi Hukum Fikih Pada Santri Pondok Pesantren As-Shofa Jubung - Syahrin, Achmad Waffiq Alfi; Muhith, Abd; Mas'ud (IJIT: Indonesian Journal of Islamic Teaching, 2025)
Learning activities are closely related to the process of seeking knowledge. This activity is very important to be carried out in human life, because humans develop knowledge and improve their lives through learning and learning. Islam as a religion that is rahmatan lil alamien requires its people to always do education by learning. Indonesia, where the majority of the people are Muslim, adheres to the madzhab of Imam Syafi'ie. This is because the first Islamic religion to enter is Islam with the Syafi'ie madzhab so that the majority of da'wah for the spread of Islam in Indonesia is Islam with the Syafi'ie madzhab. then the emphasis on learning Islamic religious education should be on the madzhab of Imam Syafi'ie. one example is the study of the book At-Tadzhib fi Adillati Matan Al-Ghoyati wa At-Taqib, a book that teaches the law of Fiqh according to Imam Syafi'ie. The focus in this research is: 1) What is the learning strategy of the book at-tadzhib fi al-ghoyati wa at-taqrib in accommodating the law of fiqh to students at As-Shofa Jubung boarding school?, 2) How is the method of learning the book at-tadzhib fi al-ghoyati wa at-taqrib in accommodating the law of fiqh to students at As-Shofa Jubung boarding school?, 3) How is the evaluation of the study of the book at-tadzhib fi al-ghoyati wa at-taqrib in accommodating law of fiqh to students at As-Shofa Jubung boarding school? To answer these problems, researchers use a qualitative approach with the type of case study. The data acquisition in this study was obtained through observation, interview, and documentation which then the data analysis process in this study using data analysis from Miles Huberman, the validity of the data will be carried out in three steps, namely source triangulation, technical triangulation and holding membercheck. The results of this research are 1) The learning strategy of the book at-tadzhib fi al-ghoyati wa at-taqrib in accommodating the law of fiqh to students at As-Shofa Jubung uses a direct strategy 2) the method of learning the book at-tadzhib fi al-ghoyati wa at-taqrib in accommodating the law of fiqh to students at As-Shofa Jubung uses the weton/sorogan method, lectures, and questions and answers 3) evaluation of the learning of the book of at-tadzhib fi al-ghoyati wa at-taqrib in accommodating the law of fiqh to students at As-Shofa Jubung two kinds of tests, namely formative and sumtive tests.